Pengaruh Mutu Produk Dan Saluran Distribusi Terhadap Target Penjualan PT. Dinamika Synergy Elemenindo - Liatania Liatania; Syawaluddin Syawaluddin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research was conducted on consumer who work at PT. Dinamika Synergy Elemenindo. The purpose of this study was to determine and analyze the effect of product quality and distribution channels on sales targets. The population and sample in this study amounted to 40 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously product quality and distribution channels have a positive and significant effect on the sales target of PT. Dinamika Synergy Elemenindo. Partially, product quality affects the sales target of PT. Dinamika Synergy Elemenindo. Partially, the distribution channel has a positive and significant effect on the sales target of PT. Dinamika Synergy Elemenindo. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.499 which means that product quality and distribution channels can explain the sales target of 49.9% and the remaining 50.1% is influenced by variables not examined such as: sales location, price perception, market segmentation, etc